Relationship between Game Location and Match Result with the Amount of Aggression: Iranian Premier League Football Teams - Farhad Alahvisi; Mohammad Maleki; Farid Zand Salimi (The Society of Aging and Physical Activity (SAPA), 2015)
The purpose of this study was to investigate the relationship between game location (host advantage), match result (win, lose or tie) and the level of aggression in football teams of the Iranian Premier League. The study population consisted of Premier League Football teams (League XIII), and 60 matches (related to 4 teams) that were available for the researcher, were selected as the sample. The current study can be regarded as applied and descriptive, in terms of purpose and data collection, respectively. In order to collect data, the match videos of selected teams were studied, then the results of the observations were written and recorded using Roberts et al. (1999) aggression model. The results showed that no significant difference was found between teams' aggression in host and guest matches (p>0.05). Also, a significant difference was observed between aggression and match result and the behaviors were more in lost matches (p< 0.05). In fact, mental stress caused by the loss resulted to more aggression to win. Hence, a match result, physical aggression and players' position led to significant difference in players' aggression. Therefore, the control and management of aggressive behaviors, especially at the time of failure will result in improved performance and efficiency of football teams. Also, these behaviors can be minimized by providing necessary training on anger management and negative emotions control among players.